PRINCIPALS’ ADMINISTRATIVE STRATEGIES FOR THE ACHIEVEMENT OF QUALITY ASSURANCE IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE - OHAMOBI, Ifunanya N.; ANASIUDU, Ifeoma Blessing (Int’l Journal of Education Research and Scientific Development, 2024)
This study sought to examine principals’ administrative strategies for the achievement of quality assurance in public secondary schools in Anambra State. The design of the study was a descriptive survey. Three research questions and three null hypotheses guided the study. The population of the study comprised 7178 principals and teachers. The sample of the study consisted of 202 principals and teachers. Questionnaire was used as instrument for data collection. Mean and standard deviation were used to answer the research questions, while t-test statistics was used to test the null hypotheses at 0.05 level of significance. The findings of the study indicate that principals’ planning strategies significantly influence the achievement of quality assurance in secondary schools in Anambra State, principals’ organizing strategies significantly influence the achievement of quality assurance in secondary schools in Anambra State, principals’ decision-making strategies significantly influence the achievement of quality assurance in secondary schools in Anambra State. The study concluded among others that proper use of the documented planning, organizing and decision-making strategies by school principals could promote quality assurance in secondary school administration. From the findings and implications of the study, it was recommended among others that state government should appoint capable and qualified persons as principals in order to implement the documented administrative strategies for quality assurance in secondary school administration.